1999
DOI: 10.1007/s001980050158
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Variables in Pre- and Postmenopausal Women: Reconciling the Calcium and Estrogen Hypotheses

Abstract: There is controversy as to whether the rise in urinary calcium at the menopause is the cause or the result of the rise in bone resorption at that time. In an attempt to resolve this issue, we have compared the relevant biochemical variables in 102 premenopausal volunteers (mean age 37 years; range 21-52) and 86 apparently normal postmenopausal women (mean age 55 years; range 40-60). We measured the fasting serum calcium, creatinine, proteins, electrolytes and intact parathyroid hormone (PTH), and the urinary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 42 publications
4
37
3
Order By: Relevance
“…Dietary intake of meat (combination of animal meat, poultry and fish) of the ‡70-year-old women (133 g/day) was, however, only insignificantly (P>0.10) lower than that of younger people (e.g., 175 g/day for 15-19-year-old women, at which the intake was highest among women of a whole age range) due to wide inter-individual variation (the ASD being nearly equal to the AM) (Ministry The present analysis made it clear that menopause is an influential factor of CR, the power being comparable to that of age (Table 7). The finding that urinary CR was lower among post-menopausal women than among pre-menopausal women was as previously reported; for example, Nordin et al (1991) observed that average CR in spot urine samples from post-menopausal women was significantly (P<0.01) lower than that from pre-menopausal subjects, and the same was also the case when CR levels were compared in 24-h urine samples, although statistical power for the difference varied depending on the studies (Nordin et al 1993(Nordin et al , 1999.…”
Section: Discussionsupporting
confidence: 65%
“…Dietary intake of meat (combination of animal meat, poultry and fish) of the ‡70-year-old women (133 g/day) was, however, only insignificantly (P>0.10) lower than that of younger people (e.g., 175 g/day for 15-19-year-old women, at which the intake was highest among women of a whole age range) due to wide inter-individual variation (the ASD being nearly equal to the AM) (Ministry The present analysis made it clear that menopause is an influential factor of CR, the power being comparable to that of age (Table 7). The finding that urinary CR was lower among post-menopausal women than among pre-menopausal women was as previously reported; for example, Nordin et al (1991) observed that average CR in spot urine samples from post-menopausal women was significantly (P<0.01) lower than that from pre-menopausal subjects, and the same was also the case when CR levels were compared in 24-h urine samples, although statistical power for the difference varied depending on the studies (Nordin et al 1993(Nordin et al , 1999.…”
Section: Discussionsupporting
confidence: 65%
“…[16] The present study showed significant reduction in serum calcium in premenopausal hypertensive patients which is in agreement to other research findings. [17] An increase in concentration of serum calcium was observed in postmenopausal hypertensive women and this may be due to higher filtered load of calcium mainly because of their reduced reabsorption of calcium. A direct effect of Section: Biochemistry calcium is reported on the peripheral vascular tone.…”
Section: Discussionmentioning
confidence: 99%
“…[18] A research study by Nordin et al have stated that urinary calcium in post-menopause is increased because of two components increased filtered load and reduced tubular re-absorption. [17] A rise in the level of serum calcium, potassium and parallel decrease in the level of serum sodium was observed after supplementing ACE-inhibitor, enalapril and β-blocker, atenolol which is necessary for decreasing blood pressure in pre and postmenopausal women. [19] A study conducted for analysis of relationship between sodium status and ACE-inhibitor efficacy reported that sodium depletion boosts renin secretion from the juxtaglomerular cells which leads to increase in the hypotensive effect of ACE-inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…These results were comparable to a study by Fowler 23 , where ultrasound identified hydronephrosis in 95%, ureteral dilation in 89% and perirenal fluid in 23% of the patients as in present study. As previously highlighted, due to low individual sensitivities and specificities, the KUB should always be paired with another imaging modality such ultrasound 24 . In the present study X-ray KUB when combined with USG, correctly diagnosed urolithiasis in 35 (70%) of the 39 patients with urolithiasis.…”
Section: Discussionmentioning
confidence: 99%